Função da musculatura do assoalho pélvico em gestantes e puérperas: avaliação manométrica e efeito da massagem perineal - Reis, Bianca Manzan (Universidade Federal de São Carlos, 2021)
Pregnancy and childbirth are considered predictors of Pelvic Floor Muscle (PFM) disorders. Preventive or treatment strategies involve the correct contraction of this musculature and perineal massage during pregnancy to reduce the chance of perineal trauma. However, to date, a gold standard method for evaluating PFM and avoiding or minimizing perineal trauma has not been established in the literature. This thesis consists of two studies with the following objectives: Study I: The objective was to evaluate measures of diagnostic accuracy of the PeritronTM manometer to distinguish pregnant women who were able or not to sustain and cranially elevate the pelvic floor muscles during maximal voluntary contraction. This is a cross-sectional study in which the diagnostic accuracy was evaluated to determine variables that distinguish primiparas in the third trimester of pregnancy, who have or not the ability to contract PFM correctly, through vaginal palpation, classified by the Modified Oxford Scale and vaginal manometry (PeritronTM) as a reference test, based on sensitivity, specificity, likelihood ratio, Receiver Operator Characteristic (ROC) and Area Under the Curve (AUC) curve. In conclusion, the variables that showed the best results of diagnostic accuracy to distinguish women who perform a correct PFM contraction were the peak, the mean, the onset time of the contraction (gradient), the duration of the contraction time and the area under the curve. Study II: The main objective was to compare the effects of perineal massage on the pelvic floor muscle function of postpartum primiparae submitted to cesarean or vaginal delivery. The secondary objective was to assess the prevalence of urinary symptoms and the risk of female sexual dysfunction among women who underwent perineal massage and the control group. This is a controlled clinical trial, which evaluated the effects of perineal massage (performed in the third trimester of pregnancy) on pelvic floor muscle function 60 days after delivery of primiparae who underwent cesarean section or vaginal delivery. Initially, the pregnant women were divided into two groups: perineal massage, in which they were instructed to start the technique from the 34th gestational week, and a control group, which received general guidance without performing PFM-related techniques. In conclusion, women who underwent perineal massage had better pelvic floor muscle function after delivery when compared to women in the control groups, regardless of the route of birth.
Function of the pelvic floor musculature in pregnant and puerperal women: manometric evaluation and effect of perineal massage
Keywords: Saúde da mulher; Assoalho pélvico; Massagem; Gestação; Pós-parto; Manometria; Avaliação de resultados e processos; Women's health; Pelvic floor; Massage; Pregnancy; Postpartum; Manometry; Results and processes evaluation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL